The Emerging Perspective of Morphine Tolerance: MicroRNAs - Teng J. Zhang; Yong Qiu; Zhen Hua (Pain Research and Management)
Morphine has unfavorable side effects including analgesic tolerance. Morphine tolerance counteracts analgesic efficacy and drives dose escalation. The mechanisms underlying morphine tolerance remain disputed, which has prevented the development of therapies to maximize and sustain analgesic efficacy. Morphine tolerance is an adaptive process induced by chronic morphine that has been shown to result from complex alterations at the molecular level with μ opioid receptors (MORs), as well as at the synaptic, cellular, and circuit levels. MicroRNAs are noncoding RNAs that have been proposed to regulate gene expression and degradation at the posttranscriptional level, including the MOR, as well as synaptic plasticity and neuroplasticity, in both the peripheral and central nervous systems. This review covers some of the most striking microRNA functions involved in morphine tolerance and presents limitations on our knowledge of their physiological roles.